Constitutional Educational Justice a Review on Education Budget: Nowadays Challenges - Agusweka Poltak Siregar; I Gusti Ayu Ketut Rachmi Handayani (Jurnal Hukum dan Pembangunan Ekonomi, 2025)
One of the contents of the Constitution is the guarantee of human rights, constitutional rights as citizens. These rights are contained in the Constitution comprehensively. In the 1945 Constitution there is one chapter, namely Chapter XA which contains guarantees for human rights. One of the constitutional rights of citizens guaranteed by the 1945 Constitution is the right to education (the right to education). This right is mentioned in particular in Article 28C paragraph (1) regarding the right to receive education and benefit from science and Article 28E paragraph (1) which talks about the right to choose education and teaching.